Efektivitas Pendekatan Teaching at The Right Level (TaRL) dalam Meningkatkan Pemahaman Peserta Didik Terhadap Materi Seleksi Benih - Astuti, Anik Fitri; Nurwahyunani, Atip; Cahyati, Zubaidah Gesit (Universitas PGRI Semarang, 2025)
This research was conducted at SMKN 1 Bawen with the research population consisting of all students of class XI ATPH A. The study aimed to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach in improving students' understanding of seed selection material. The instruments used in this research were pretest and posttest assessments. The TaRL approach was implemented by grouping students based on their initial understanding as measured by pretest scores. Students were categorized into three groups: proficient, sufficient, and low. During the discussion process, teachers provided intensive guidance to the low-category group, while students in the proficient and sufficient categories were given additional challenges in the form of questions designed to enhance critical thinking, creativity, and problem solving. Data analysis was performed using the N-Gain test and the Wilcoxon Signed-Rank Test. The analysis results showed an N-Gain value of 0.6198, indicating a moderate level of effectiveness of the TaRL approach in improving the understanding of seed selection material among students of class XI ATPH A. Additionally, the Wilcoxon Signed-Rank Test revealed that out of 21 students, 15 experienced an increase in their scores from pretest to posttest, with an average score increase of 10.93. The Wilcoxon test's significance value of 0.005 that can indicated significant difference between pretest and posttest. Based on these findings, it can be concluded that the Teaching at the Right Level (TaRL) approach is effective in improving students' understanding of seed selection material in class XI ATPH A.